2009
DOI: 10.1152/ajpheart.00165.2008
|View full text |Cite
|
Sign up to set email alerts
|

PDGF-DD, a novel mediator of smooth muscle cell phenotypic modulation, is upregulated in endothelial cells exposed to atherosclerosis-prone flow patterns

Abstract: GK. PDGF-DD, a novel mediator of smooth muscle cell phenotypic modulation, is upregulated in endothelial cells exposed to atherosclerosis-prone flow patterns. Am J Physiol Heart Circ Physiol 296: H442-H452, 2009. First published November 21, 2008 doi:10.1152/ajpheart.00165.2008.-Platelet-derived growth factor (PDGF)-BB is a well-known smooth muscle (SM) cell (SMC) phenotypic modulator that signals by binding to PDGF ␣␣-, ␣␤-, and ␤␤-membrane receptors. PDGF-DD is a recently identified PDGF family member, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
52
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 42 publications
1
52
0
Order By: Relevance
“…These signaling pathways induce the proliferation, migration, apoptosis, and osteoblastic differentiation of VSMCs, and altered VSMCs play a major role in vascular calcification 35, 36. Recent studies have shown that high shear stress induces apoptosis of VSMCs through nitric oxide released by endothelial cells,37 and low shear stress upregulates the proliferation and migration of VSMCs via platelet‐derived growth factor and transforming growth factor secreted by endothelial cells 38. Therefore, ECF excess may also be involved in vascular calcification through the cross‐talk between endothelial cells and VSMCs.…”
Section: Discussionmentioning
confidence: 99%
“…These signaling pathways induce the proliferation, migration, apoptosis, and osteoblastic differentiation of VSMCs, and altered VSMCs play a major role in vascular calcification 35, 36. Recent studies have shown that high shear stress induces apoptosis of VSMCs through nitric oxide released by endothelial cells,37 and low shear stress upregulates the proliferation and migration of VSMCs via platelet‐derived growth factor and transforming growth factor secreted by endothelial cells 38. Therefore, ECF excess may also be involved in vascular calcification through the cross‐talk between endothelial cells and VSMCs.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism involved is that low shear stress increases endothelial PDGF expression [116][117][118] and the upregulated expression of PDGF-DD in ECs mediates VSMC phenotypic modulation [119,120]. High shear stress protects ECs, even shear exceeding 1500 dyn cm 22 did not cause gross injury or denudation [121].…”
mentioning
confidence: 99%
“…In addition, in vivo blockade of PDGF-BB or PDGFR-␤ reduces SMC migration into neointimal lesions after vascular injury and decreases SMC accumulation and fibrous cap formation within developing atherosclerotic plaques in mice (25,37,54,66,69). Recent studies have demonstrated that PDGF-DD, a newly discovered PDGF isoform that is a more selective agonist of the PDGFR-␤, also promotes SMC phenotypic modulation through repressing SMC differentiation marker gene expression and increasing SMC proliferation and migration (5,13,38,73). Genetic deletion of the PDGFR-␤ in cultured SMCs abrogated PDGF-DD-and PDGF-BB-induced repression of SMC differentiation marker genes, suggesting that these effects of PDGF on SMC phenotype are mediated via PDGFR-␤ activation (73).…”
mentioning
confidence: 99%
“…Recent studies have demonstrated that PDGF-DD, a newly discovered PDGF isoform that is a more selective agonist of the PDGFR-␤, also promotes SMC phenotypic modulation through repressing SMC differentiation marker gene expression and increasing SMC proliferation and migration (5,13,38,73). Genetic deletion of the PDGFR-␤ in cultured SMCs abrogated PDGF-DD-and PDGF-BB-induced repression of SMC differentiation marker genes, suggesting that these effects of PDGF on SMC phenotype are mediated via PDGFR-␤ activation (73). These results suggest that multiple PDGF isoforms acting at the PDGFR-␤ mediate SMC phenotypic modulation in a way that resembles the classically defined switch from a contractile to a synthetic state observed within atherosclerotic lesions in vivo (10,64).…”
mentioning
confidence: 99%